2020
DOI: 10.3390/su12030817
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Resilience and Mapuche Community Based Tourism in the Pre-Cordilleran Territories of Panguipulli, Southern Chile

Abstract: In Latin America, community resilience has emphasized the solidarity capacities and strengths of indigenous communities to face and proactively overcome adversities derived from political and social violence. This is the case of Mapuche communities linked to community based tourism in pre-cordilleran areas of southern Chile. This article analyzes tourism experiences of these Mapuche communities, based on a qualitative exploratory and descriptive approach, in order to determine their relationship with community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 20 publications
0
5
0
5
Order By: Relevance
“…Three components Acute shocks (natural and man-made) [54] Climate-related disasters [78] Community based tourism [101] Disasters [55] Economic development and social capital [110] Food, energy, and water [57] Health, safety, and health equity [112] Local economy, job, and environment [40] Private sector enterprises [46] Risks and threats [45] Urban planning and policy [69] Four components…”
Section: Number Of Components Focus Year Referencementioning
confidence: 99%
See 2 more Smart Citations
“…Three components Acute shocks (natural and man-made) [54] Climate-related disasters [78] Community based tourism [101] Disasters [55] Economic development and social capital [110] Food, energy, and water [57] Health, safety, and health equity [112] Local economy, job, and environment [40] Private sector enterprises [46] Risks and threats [45] Urban planning and policy [69] Four components…”
Section: Number Of Components Focus Year Referencementioning
confidence: 99%
“…Qualitative All-hazards environment 4-stage process for identifying issues, solving problems, and planning activities [79] Climate risks 6-phase process (4 phases for preparation and 2 phases for implementation and monitoring) [61] Community based tourism Relationship between tourism experiences with community resilience processes [101] Evacuation route planning and design Limits of punctual treatments and impacts on dimensions of urban walkability [63] Man-made and natural disasters 6-stage process with detailed guidance, tools, and resources identified for each module [89] National health security Roadmap used as a starting point to develop local community resilience strategy [77] Soil erosion Impacts on soil erosion based on social, psychological, and cultural parameters [104] Stresses accumulate and sudden shocks 4 categories, 12 goals, 52 indicators, and 156 variables for city resilience [49] Tsunami Strength and weakness of tsunami preparedness based on eight resilience elements [105] Analysis of resilience capacities and resources activated to cope with disaster [99] Quantitative Acute shocks (natural and man-made) Resilience scores for preliminary (from 0 to 30) and detailed assessment (from 0 to 180) [54] Climate change Space time dynamic resilience measure (ST-DRM) [51] Disasters Disaster resilience score ranging between 22 and 110 [84] Community disaster resilience index for 4 capital indices across 4 management phases [82] A single, scalar measure combined from six multidimensional components [83] Resilience index based on the percentage of check marks and the number of Yes answers [90] Disaster-resilience index score based on process-and outcome-indicator scores [98] Economic development and social capital Composite scores of economic development, social capital and community resilience [110] Health, safety, and health equity Top three priorities to increase health and safety and reduce health inequities [112] Natural hazards Composite resilience index ranging between 0 and 100 [108] Rural diversity Rural diversity index ranging between 0 and 1 [43] Shocks and adverse events Overall rank along with vulnerability, adaptive capacity, and resilience scores [60] Hybrid Community resources Community portrait involving community perceptions, attitudes, feelings, and others [37] Community assets Toolkit for specific resources and acti...…”
Section: Focus Outcome Referencementioning
confidence: 99%
See 1 more Smart Citation
“…The interest of human agency and its role in SES dynamics is gaining momentum [64][65][66]. In the context of tourism, recently published works study resilience at the community level from an individual/household approach [67,68], as well as a collective point of view [56,[69][70][71][72][73][74]. These studies consider human agency from two theoretical perspectives, viz.…”
Section: Sess and Resilience At The Community Levelmentioning
confidence: 99%
“…Studies in contexts other than Latin America have found links between high levels of ethnic identity and low symptoms of depression, thoughts of suicide, and history of suicide attempts ( Cheng et al, 2010 ). In the national context, one study found that there is a positive relationship between Mapuche ethnic identity, well-being, and resilience ( Pilquimán et al, 2020 ). The results of these studies reinforce the idea that positive ethnic identity is a protective factor in the emergence of depressive symptoms and suicidal ideation ( Tereucán et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%